The Contribution of Endmembers to Mixtures of Leaf Leachates and Riverine DOM can be Determined by Measuring Their Size and Fluorescence Properties - Cuss, C. W.; Guéguen, C. (Frontiers in Environmental Chemistry, 2022)
The molecular mass distribution (MMD) and fluorescence properties of dissolved organic matter (DOM) are important characteristics for tracing and predicting its pathways, processes, and fate in aquatic systems. For the first time, asymmetrical flow field-flow fractionation (AF4) with coupled absorbance and fluorescence detectors was used to determine the contribution of endmembers to three mixtures of leaf leachate and riverine DOM in various proportions. Parallel factor analysis (PARAFAC) and fractogram deconvolution were used to decompose and distinguish the size distributions and fluorescence excitation-emission matrices (EEMs) of mixture constituents. It was determined that: 1) Both size and optical properties were conservative tracers in mixtures; 2) Fractogram deconvolution was extremely helpful for discriminating endmember size properties; 3) The contributions of endmembers to overall DOC concentration were accurately estimated using both the proportion of a humic-like PARAFAC component (0.93 < R2 < 1.00), and the ratios of deconvoluted peaks (0.88 < R2 < 0.98). The fluorescence at the peak maximum of the MMD was lacking in protein-/polyphenol-like and microbial humic-like fluorescence compared to the whole sample (-11 ± 9 and -10 ± 7 %, respectively); however, the contribution of endmembers to the MMD (A254) were also effectively predicted using both the proportion of a microbial humic-like PARAFAC component (0.91 < R2 < 0.98) and the ratio of deconvoluted peaks (0.94 < R2 < 0.98).